The great river : the making and unmaking of the Mississippi - Upholt, Boyce (W.W. Norton & Company, 2024)
In this landmark work of natural history, a journalist tells the epic story of the Mississippi River and the centuries of efforts to control it, which have damaged its once-vibrant ecosystems, carrying readers along the river's last remaining backchannels and exploring how scientists hope to restore what has been lost.